EVALUATION OF THE QUALITY OF LIFE IN ADULT INDIVIDUALS SUBMITTED TO SURGICAL TREATMENT DUE TO TEARS OF THE ROTATOR CUFF. (Fiep Bulletin - online, 2014)
INTRODUCTION: The tears of  the rotator  cuff occur with  a considerable part of the population, accounting  for 11 to 25% of the  patients  treated in physiotherapy  clinics. The current treatments focus on  the surgery and the physiotherapy as important instruments to  check out the therapeutic  results. However, these measures, are sometimes not sufficient and the patients continue having  functional-kinetic  problems after the treatment.   GOAL: to evaluate the quality of life of adult individuals submitted to surgical treatment due to tears of the rotator cuff;   check out  the results of the physiotherapeutic and surgical treatment after the  surgery of tears in the rotator cuff  and its influence on the quality of life. METHODS:  The methods that were used  are: the the quality of life evaluation questionnaire from World Health Organization Instrument of Assess Quality of Life - Bref (WHOQOL-BREF) and the functional scale from the University of California at Los Angeles (UCLA).  The sample was made up of 20 people of both genders, between 29 and 73 years old, submitted to surgical treatment, due to tears of the rotator cuff with the same surgeon, using the mini-open repair and who received  physiotherapeutic treatment in the year of 2005.  RESULtS: The results found in the accounting of the data of the questionnaire WHOQOL-BREF showed there to be no statistical  difference in the physical, Social relation, psychological and Environment domains.  The UCLA scale identified level of satisfaction in functionality in 85% of the individuals. CONCLUSION: The surgical treatment of the Rotator cuff, associated to the physiotherapeutic treatment  using physical resources: Ultrasound scan, Short waves, TENS e  kinetic therapy   has good results and gets high level of satisfaction of the patients relating to the final results, since in 85% of the sample showed good satisfaction level(30%) and excellent (55%), in this way no alteration of the quality of life of these patients were found.
Keywords: quality of life; rotator cuff; surgical treatment